Detection of radio interference in the UHF amateur radio band with the Serpens satellite. Issue 2 (15th January 2022) - Quintana-Diaz, Gara; Nodar-López, Diego; González Muíño, Alberto; Aguado Agelet, Fernando; Cappelletti, Chantal; Ekman, Torbjörn
Abstract: High packet losses when uplinking commands to small satellites have been reported in the UHF amateur band (430–440 MHz) since late 2013. Measurements of the uplink radio environment have shown high levels of in-band interference in previous works, but public measurement results are limited. Average interference levels are usually measured over some time to build heat maps. In this paper, the analysis is focused on sustained interference over a 24 ms time window using a maximum-minimum method. New heat maps and interference power distributions over Europe, Africa, the Middle East and the Americas were obtained using this method on measurements from the Serpens satellite. One of the missions of Serpens was to test an in orbit store-and-forward communication system to exchange short messages with ground sensors for disaster monitoring. The satellite operators had difficulties commanding the satellite due to interference, causing bit errors in uplink packets. Interference power of up to −70 dBm was detected during in-orbit measurements over Europe and North America, while expected received power from the ground stations was not more than −80 dBm. High power space-object tracking radars on the ground operating in the 420–450 MHz band could be the cause, but further measurements are required to verify this. Characterizing this interference can help develop mitigation techniques for future satellite communication systems.